VR FOR GOOD: A SOCIO-PRENEURSHIP MODEL UTILIZING VIRTUAL REALITY EXPOSURE THERAPY (VRET) FOR AFFORDABLE MENTAL HEALTH SERVICES - Ethan Thompson; Sofia Lim; Ingrid Olsson (Yayasan Adra Karima Hubbi, 2025)
The global mental health crisis continues to escalate, with millions of individuals facing barriers to accessing affordable care. Traditional mental health services, while effective, are often inaccessible due to high costs, geographic barriers, and limited availability. This research proposes a socio-preneurship model that leverages Virtual Reality Exposure Therapy (VRET) as a scalable, cost-effective solution to address these challenges. The study aims to explore the feasibility and effectiveness of utilizing VRET within a socio-preneurship framework to provide affordable mental health services to underserved populations. A mixed-methods approach was employed, combining quantitative measures of anxiety and stress reduction with qualitative interviews to assess user satisfaction and engagement. Participants were divided into a VR therapy group and a control group receiving traditional therapy. The results demonstrated significant improvements in anxiety and stress levels for the VR therapy group compared to the control group, alongside higher levels of user engagement and satisfaction. The study concludes that VRET, when integrated into a socio-preneurship model, offers a viable, accessible, and effective solution to providing mental health services in underserved communities. This approach not only improves mental health outcomes but also creates sustainable, scalable systems for addressing mental health disparities.